Little big soldier [videorecording (DVD)] - Ding, Sheng, 1970-; Cheng, Long, 1954-; Wang, Lihong, 1976-; Yoo, Seungjun; Lin, Peng, 1986-; Du, Yuming, 1958-; Jin, Song, 1973 October- (Well Go USA, 2011)
An old soldier kidnaps a young general of an enemy state and takes him on a long journey to collect the reward.